KECERDASAN SPIRITUAL DAN KOMITMEN ORGANISASI MAHASISWA PENGURUS ORGANISASI - Yuliani, Tri; Komalasari, Shanty (Faculty of Ushuluddin and Humanities, 2019)
Lack of organizational commitment often occurs among students who are administrators of the organization; they are still less able to set rules for themselves. These abilities are related to how one judges and interpret each action or commonly referred to as spiritual intelligence. This study aims to examine the relationship between spiritual intelligence and organizational commitment. The population in this study amounted to 919 people, with a sample of 92 administrators of UKK and UKM in the 2017/2018 period at UIN Antasari Banjarmasin. The sampling technique in this study uses probability sampling with a type of sample random sampling. The instrument of data collection uses the scale of organizational commitment and spiritual intelligence of the Likert model and analysis using Product Moment correlation with the help of SPSS 21.0. Based on the calculation results show that the level of organizational commitment and spiritual intelligence of students is classified as moderate. The results of the correlation test indicate a significant positive relationship between the two variables (p = 0.002, p <0.05). The higher the spiritual intelligence, the higher the student's organizational commitment and vice versa, the lower the spiritual intelligence, the lower the student's organizational commitment.